Radiotherapy and checkpoint inhibitors: a winning new combination?. (10th April 2018) - Ko, Eric C.; Formenti, Silvia C.
Immune checkpoint blockade has recently emerged as an important therapeutic approach to the management of malignancies across multiple disease settings. Concomitantly, there has been an increasing appreciation for the role of radiotherapy in eliciting and promoting tumor-directed immune responses. In this review, we discuss the clinical evidence to date on combinations of radiotherapy with immune checkpoint inhibitors, both from the standpoint of safety and efficacy. We highlight important but yet-unanswered questions for this combination approach, as well as their implications for future prospective studies.